Analysis Of The Effect Of Flexible Working Arrangements On Employee Performance: The Role Of Work-Life Balance And Job Satisfaction As Mediating Variables In The Banking Industry - Johannes P. Kumagaya; Fitri Kurniawati; Fransiska Ekobelawati; Herry Syafrial; Darmun (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The changing paradigm of the modern workplace post-pandemic and the rapid digital transformation have encouraged the banking sector to adopt Flexible Working Arrangements (FWA) schemes. This study aims to comprehensively analyze the influence of Flexible Working Arrangements on employee performance in the banking industry, by exploring the mediating role of Work-Life Balance and Job Satisfaction. Using a quantitative explanatory approach with a comparative and path analysis research design, data were collected from a sample of banking employees implementing flexible work schemes. The results of the theoretical and scientific study indicate that the implementation of FWA not only makes a significant direct contribution to improving employee performance but also transforms the psychological dynamics of the workplace by improving work-life balance and job satisfaction. Work-Life Balance and Job Satisfaction are proven to act as partial mediators that strengthen the positive relationship between work flexibility and employee productivity. These findings confirm that strategically managed flexibility, supported by responsive technological infrastructure and a supportive organizational culture, is an important catalyst in maintaining operational resilience, talent retention, and achieving sustainable performance in the modern banking industry